Revision of the Dependency Dimension of the Dimensional Clinical Personality Inventory - Carvalho, Lucas de Francisco; Pianowski, Giselle (Paidéia (Ribeirão Preto), 2015)
The assessment of personality in pathologic levels is a field that requires investment. This study aimed to review the Dependency Dimension of the Dimensional Clinical Personality Inventory (IDCP). The study was conducted through the development of new items based on the literature, and by investigating the psychometric properties in a sample of 199 participants, aged between 18 and 54 years (M = 26.37, SD = 8.13), 71.4% female, who responded to the IDCP, the NEO-PI-R, and the PID-5. The first step resulted in 57 items that were tested psychometrically. Then, the dimension remained with 18 items, with internal consistency of .89, and three factors: Self-devaluation, Avoidance of abandonment, and Insecurity, with internal consistency between .79 and .91. The expected correlations coefficients were found between the Dependency dimension and the correlated dimensions and facets of the NEO-PI-R and PID-5. The results evidence the adequacy of the revised dimension.